Maduración pulmonar fetal nuevas evidencias - Rojas Pérez, Lino Arturo (2023)
Introduction. The birth of a premature newborn (NB) increases neonatal morbidity and mortality due to the immaturity of the different organs; the lower the gestational age at birth, the greater the risk of complications may occur. Objectives. Determine the best treatment for fetal lung maturation to reduce complications in premature newborns, according to the best available evidence. Methodology. The clinical question under the PICO format was used: What is the best treatment for fetal lung maturation in patients at high risk of preterm birth? The population is pregnant women at high risk of preterm birth, the intervention is the administration of corticosteroids, the comparison is the non-administration of corticosteroids, and the result is the reduction of complications due to prematurity. Results. To carry out this review, 1,422 articles were obtained, of which 1,372 were discarded for not being within the inclusion criteria and 47 articles were obtained, of which 1 article was eliminated because it was duplicated. In the review process and preparation of this research 46 scientific articles were used. Discussion. The administration of glucocorticoids to pregnant women who are at high risk of preterm delivery in the next 7 days decreases the risk of several of the complications that could occur in a premature newborn. Conclusions. Corticosteroids that are recommended for women at risk of preterm labor between 23 weeks and 36 weeks 6 days are betamethasone or dexamethasone given intramuscularly.